Related Factors with School Age Children’s Iodine Status in Indonesia - Nurul Lathifah; Sri Sumarmi (Jurnal Berkala Epidemiologi, 2018)
Background: The prevalence of iodine deficiency as the cause of Iodine Deficiency Disorders (IDD) in children in Indonesia increased from 12,9% in 2007 become 14,9% in 2013. The assessment of IDD is by iodine status via measuring Urine Iodine Excretion (UIE) and level of iodine salt. Purpose: The aim of this study was to analyze the correlation between children’s characteristics, social economic characteristics of parents, and level of iodine in salt with iodine status in school age children in Indonesia. Methods: The research design of this study was secondary data analysis. This study used data of Basic Health Research (Riskesdas) 2013. Data were analyzed by chi square, eta, and spearman correlation test. Results: The research showed that factor that there was a significant correlation with iodine status in school age children in Indonesia are children’s gender (p = 0,01), father’s education (p = 0,01; r = 0,09), mother’s education (p = 0,01; r = 0,11), father’s occupation (p = 0,01; r = 0,12), mother’s occupation (p = 0,01; r = 0,09), and level of iodine in salt (p = 0,01). Children’s age was no significant correlation with iodine status in school age children (p = 0,81). Conclusion: There was a correlation between children’s gender, social economic characteristics of parents, and level of iodine in salt with iodine status in school age children in Indonesia.